VECTOR AUTOREGRESSIVE (VAR) UNTUK PERAMALAN HARGA SAHAM PT INDOFOOD SUKSES MAKMUR Tbk. - Maruddani, Di Asih; Safitri, Diah (MATEMATIKA, 2008)
In simultaneous or structural equation models, if there is true simultaneity among a set of variables, they should not be any apriori distinction between endogenous and exogenous variables. It is in this spirit of the VAR models. We study stock value simultaneous model at PT Indofood Sukses Makmur Indonesia Tbk, for the period of 1998–2005. Variables in stock value simultaneous models are stock value, Return of Assets (ROA), Debt to Equity Ratio (DER), and Earning Per Share (EPS). The data is obtained from the Indonesian Capital Market Directory, Jakarta Stock Exchange and PT Indofood Sukses Makmur Indonesia Tbk. Financial Statement. The empirical results showed that the variables under consideration can be said to be integrated of order one, and the residuals have independent and normal distribution. With AIC and SC values, we conclude that each equations contains four lag values of Stock Value, ROA, DER, and EPS. The estimated VAR model can be used for forecasting the future values of stock value. In this study, we forecast the stock value from 2006:1 until 2007:12.